Association of HLA-B∗38:02 with Antithyroid Drug-Induced Agranulocytosis in Kinh Vietnamese Patients - Mai Phuong Thao; Pham Vo Anh Tuan; Le Gia Hoang Linh; Lam Van Hoang; Phan Huu Hen; Le Tuyet Hoa; Hoang Anh Vu; Do Duc Minh (International Journal of Endocrinology)
Background. HLA-B∗38:02 has been shown to be associated with antithyroid drug-induced agranulocytosis in Asian patients. Methods. HLA-B∗38:02 was analyzed by sequence-based typing in 21 patients who developed antithyroid drug-induced agranulocytosis and in 81 controls. Results. Frequency of HLA-B∗38:02 was 52.4% in agranulocytosis patients compared to 3.7% in controls (OR = 28.6, 95% CI = 6.8–120.2). Conclusions. HLA-B∗38:02 is a significant risk factor for agranulocytosis in Kinh Vietnamese patients treated with antithyroid drug.